ID #984 Integrating Treatment Approach, Histopathology, and Clinicogenomic Landscape to Predict Recurrence and Outcome in Pediatric Myxopapillary Ependymoma - Ana Aguilar-Bonilla; Sanda Alexandrescu; Erin White; Karen Wright; Nicole Ullrich; Hart Lidov; Susan Chi; Kevin Liu; Shannon MacDonald; Pratiti Bandopadhayay; Lissa Baird; Katie Fehnel; et al. (Neuro-Oncology Pediatrics, 2026)
Abstract Background Myxopapillary ependymoma (MPE) is a rare ependymoma subtype, commonly arising in the lumbosacral canal. Pediatric cases represent 8-20% of MPEs. Despite their slow-growing nature, pediatric cases demonstrate distinct clinical behavior, highlighted by higher local recurrence and dissemination rates compared to adults.[1] Characterization of pediatric MPE is essential to optimize risk stratification and management. This study evaluates clinicopathological and genomic factors that may be predictive. Methods We performed a retrospective, IRB-approved study of pediatric patients diagnosed with MPE over the past 30 years at Dana-Farber/Boston Children’s Hospital. Medical records were reviewed for clinical, surgical, pathologic, and molecular data. Central histopathologic review assessed high-risk features, including necrosis, microvascular proliferation, mitotic activity, and increased proliferative index. Analysis of available molecular data (N = 24) is underway. Results Thirty-two patients were included (median age 14.61 years; range:6.22-21.16). Ten patients (10/32; 31%) had metastatic disease at presentation. All underwent surgical resection. Of 22 patients with localized disease, 17 had gross-total resection (GTR). Two (2/32; 6.3%) received upfront radiation (1 WSI, 1 focal). Nine (9/32; 28%) had high-risk histopathologic features, three of whom had metastatic disease upfront. Median follow-up was 3.98 years (range:0.08-22.64 years). The 3- and 5-year progression-free survival (PFS) was 72.3% and 64.4%, respectively. Nine patients (9/32; 28%) experienced disease recurrence, four of whom had localized disease upfront (three GTR). Median time-to-progression for patients with localized and metastatic disease was 2.37 and 0.6 years, respectively. The 5-year OS was 100%. For patients with localized disease who underwent GTR without adjuvant RT (N = 17), high-risk histopathologic features were associated with poorer 3-year PFS (50% versus 100%; p = 0.03). Conclusions In this cohort of pediatric patients with MPE, despite excellent overall survival, a significant proportion experienced early disease recurrence. Additionally, amongst patients with localized disease treated with GTR, histopathological features may have prognostic value for PFS. 1. Fassett DR, Pingree J, Kestle JR. The high incidence of tumor dissemination in myxopapillary ependymoma in pediatric patients. Report of five cases and review of the literature. J Neurosurg. 2005 Jan;102(1 Suppl):59-64. doi: 10.3171/ped.2005.102.1.0059. PMID: 16206735. 2. Bandopadhayay P, Silvera VM, Ciarlini PDSC, Malkin H, Bi WL, Bergthold G, Faisal AM, Ullrich NJ, Marcus K, Scott RM, Beroukhim R, Manley PE, Chi SN, Ligon KL, Goumnerova LC, Kieran MW. Myxopapillary ependymomas in children: imaging, treatment and outcomes. J Neurooncol. 2016 Jan;126(1):165-174. doi: 10.1007/s11060-015-1955-2. PMID: 26468139.